2005
DOI: 10.1080/10889860590929583
|View full text |Cite
|
Sign up to set email alerts
|

Geochemical, Microbiological, and Geophysical Assessments of Anaerobic Immobilization of Heavy Metals

Abstract: Bioremediation methods that precipitate contaminants in situ as solid (mineral) phases can provide cost-effective options for removing dissolved metals in contaminated groundwater. The current field-scale experiments demonstrate that indigenous bacteria can be stimulated to remove metals by injection of electron-donating substrates and nutrients into a contaminated aquifer. Groundwater at the investigation site is aerobic and contains high levels of lead, cadmium, zinc, copper, and sulfuric acid (pH = 3.1) der… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 23 publications
1
17
0
Order By: Relevance
“…This observation implies that we may be able to remediate As contamination in situ in reducing aquifers simply by injecting SO 4 2À to stimulate microbial SO 4 2À reduction (Kirk et al, 2004). Other studies have also concluded that enhancing SO 4 2À reduction may be useful for As remediation, including Rittle et al (1995), Castro et al (1999), Jong and Parry (2003), Lee et al (2005), and Saunders et al (2005), Keimowitz et al (2007). In a field test of this strategy at a naturally contaminated site in Bangladesh, Saunders et al (2008) observed a decrease in aqueous As concentration coinciding with stimulated SO 4 2À reduction.…”
Section: Introductionmentioning
confidence: 76%
“…This observation implies that we may be able to remediate As contamination in situ in reducing aquifers simply by injecting SO 4 2À to stimulate microbial SO 4 2À reduction (Kirk et al, 2004). Other studies have also concluded that enhancing SO 4 2À reduction may be useful for As remediation, including Rittle et al (1995), Castro et al (1999), Jong and Parry (2003), Lee et al (2005), and Saunders et al (2005), Keimowitz et al (2007). In a field test of this strategy at a naturally contaminated site in Bangladesh, Saunders et al (2008) observed a decrease in aqueous As concentration coinciding with stimulated SO 4 2À reduction.…”
Section: Introductionmentioning
confidence: 76%
“…Anaerobic degradation of PAHs in subsoils or aqueous systems may be enhanced by adding suitable electron acceptors, nutrients, and surfactants (Bach, Kim, Choi, & Oh, 2005;Providenti et al, 1993;Saunders et al, 2005). For example, amendment with sulfate, nitrate, or nitrous oxide may allow denitrification-coupled degradation to occur (Annweiler et al, 2002;Van Hamme et al, 2003).…”
Section: Bioremediation Applications and Engineering Solutionsmentioning
confidence: 98%
“…At a site at Troy, Alabama, which was contaminated by Zn Cd, Pb, Cu, and sulfuric acid, Saunders et al (2005b) induced bacterial sulfate reduction by injecting sucrose and diammonium phosphate into ground water. Within 30 d, previous aer-obic ground waters had become reducing enough for sulfate reduction to commence, leading to the almost instantaneous removal of the Cu, Zn, Pb, and Cd from solution as sulfides (Fig.…”
Section: Southam and Saundersmentioning
confidence: 99%